Temporal variations in otolith elemental fingerprints of Lipophrys pholis embryos along the Portuguese coast - Roque, Mafalda Gomes (2021)
The implementation of effective measures to protect the marine environment, such as Marine Protected Areas (MPA), is becoming increasingly imperative. The study of population parameters like connectivity and dispersal, is needed to apply the appropriate measures to each particular case. A method that is currently frequently used to access these parameters is elemental fingerprint (EF). It is well known its capability to assign individuals to their site of origin across several spatial scales by creating EF maps. The possible establishment of embryonic EF maps as natal origin reference could simplify the work every time an assessment is made. However, for this to be possible, temporal stability in these signatures is imperative. Yet, not much is known about interannual variation in EF. To address this issue, this study aimed to further comprehend interannual stability in otoliths elemental fingerprint from embryos of a rocky intertidal fish, Lipophrys pholis, collected along the Portuguese coast. The results shown that there is no temporal stability in EF between years. Furthermore, no differences in multielement analysis between the three sites were evident. However, it was possible to have some level of accurate assignment to site of origin, with exception of one site. These results suggest that creation of reference embryonic EF maps to use across years may not be possible. The implication is that every time an assessment is made is recommended to create new embryonic maps.